Commercial Production and Chemical/Physical Characterization of Natural and Nutritious Coconut Sap Food Products (Cocosap Juice and Cocosap Concentrate) at Tawan-tawan, Baguio District, Davao City, Southern Mindanao, Philippines - Millicent I. Secretaria (International Coconut Community Journal, 2008)
The processing of natural and nutritious coconut sap juice and coconut sap concentrate for commercial production was conducted by the members of the Samahang Magniniyugan ng Tawan-tawan (SMT) at Barangay Tawan-tawan, Baguio District, Davao City, Southern Mindanao, Philippines from February to May, 2007. The processing of coconut sap juice and concentrate involves simple, easy to follow procedures and few equipment are required. Results of the chemical analysis revealed that coconut sap juice, an oyster-white liquid and coconut sap concentrate, a sticky, golden orange syrup has 84.3% and 25% moisture content; 0.24% and 0.94% crude protein; 18.99 and 63.79 mg/100 mg sodium (Na); 0.85 and 1.51 mg/100 g calcium (Ca) and 0.05 and 0.33 mg/100g iron (Fe), respectively indicating that these coconut sap food products are nutritious and good for one’s body. While physical (color) analysis showed that these products are pure and natural since no food coloring was detected. A partial budgeting analysis on the profitability of producing coconut sap juice and coconut sap concentrate over the traditional fermented toddy indicated an additional profit or net income of Php19,728.00 and Php21,402.00 per month, respectively (Php41= $). The benefits derived from the commercialization of the technology on coconut sap food products by the adaptors were discussed. Factors for successful adoption and commercialization of coconut sap juice and concentrate were likewise recommended.